Wing Variability in Some Andean Brown Lacewing Insects as an Adaptive Survival Strategy (Insecta, Neuropterida, Neuroptera: Hemerobiidae) - Víctor J. Monserrat; Óscar Gavira (Insects)
The variability in shape and coloration patterns associated with strategies of crypsis increases the environmental entropy and makes it more difficult for a potential predator to learn a certain prey to locate. To demonstrate this concept, we composed images of the wings of two Hemerobiidae species (Gayomyia falcata and Megalomus stangei) on a leaf background and then optically analyzed them by calculating the entropy of the images (in color as well as grayscale). For comparison, we colored the wings of Hemerobiidae artificially, and the analysis was repeated with these non-cryptic wings. The results indicate that the artificially colored wings reduce the entropy of the image, facilitating the location of the specimen, while the natural wings increase the entropy, thus hiding the presence of the specimen. In this context, the more morphological and chromatic diversity that the wings show, the greater the increase in entropy.